The Who, Why, and What of Religion - and Its Study - McCutcheon, Russell T. (History of religions, 2023)
This review article examines two recent books that each adopt different stands on the contributions to be made by theory - or perhaps better, metatheory - in the study of religion. For while one aims to cultivate the role of the scholar as being a bit of a scandalous fool, the other strongly encourages colleagues to adopt an interpretive method that, or so it is claimed, contributes to solving a variety of pressing societal problems.